UPAYA PERLINDUNGAN HUKUM TERHADAP PEKERJA RUMAH TANGGA ATAS PERJANJIAN YANG MENGANDUNG KLAUSULA EKSONERASI - Yeyet Clearesta Putri Nurjaman (Fakultas Hukum Universitas Udayana, 2023)
This research aims to find out and explain legal protection efforts for Domestic Workers due to agreements made by supplying institutions with service users, in which case the agreements contain exoneration clauses. The method in this research uses a normative juridical method which can be seen from two aspects, namely based on the juridical aspect by examining the applicable laws and regulations based on the principle of novelty. Then based on the normative aspect, by examining the problems that exist in these regulations or norms. The results of this research indicate that there is an urgency to regulate agreements made between parties, namely distribution institutions, service users and domestic workers to provide legal protection for domestic workers for agreements that contain prohibited clauses, namely exoneration clauses.